2004
DOI: 10.1007/s00421-004-1193-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concurrent aerobic and resistance circuit exercise training on fitness in older adults

Abstract: The purpose of this study was to determine the physiological effects of a programmed accommodating circuit exercise (PACE) program consisting of aerobic exercise and hydraulic-resistance exercise (HRE) on fitness in older adults. Thirty-five volunteers were randomly divided into two groups [PACE group (PG) 8 men and 10 women, 68.3 (4.9) years, and non-exercise control group (CG) 7 men and 10 women, 68.0 (3.4) years). The PG participated in a 12-week, 3 days per week supervised program consisting of 10 min warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
20

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 36 publications
(43 reference statements)
8
68
0
20
Order By: Relevance
“…Abernethy (19) aplicou um treino aeróbio contínuo de baixa intensidade e outro intervalado de alta intensidade, enquanto Sporer e Wenger (17) , testaram a influência de intervalados de alta intensidade e contínuo sub-máximo conduzido em cicloergômetro no desempenho da força. Portanto, pode-se verificar que existe um agudo do treino aeróbio no TF envolvendo idosas ativas fisicamente, vale ressaltar que apenas dois trabalhos (6,7) verificaram o efeito crônico do treinamento concorrente de aeróbio e força em relação aos seus benefícios para a otimização do treinamento funcional na terceira idade.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Abernethy (19) aplicou um treino aeróbio contínuo de baixa intensidade e outro intervalado de alta intensidade, enquanto Sporer e Wenger (17) , testaram a influência de intervalados de alta intensidade e contínuo sub-máximo conduzido em cicloergômetro no desempenho da força. Portanto, pode-se verificar que existe um agudo do treino aeróbio no TF envolvendo idosas ativas fisicamente, vale ressaltar que apenas dois trabalhos (6,7) verificaram o efeito crônico do treinamento concorrente de aeróbio e força em relação aos seus benefícios para a otimização do treinamento funcional na terceira idade.…”
Section: Discussionunclassified
“…Assim, sugere-se que tal efeito inibitório encontrado de forma constante na literatura pode estar associado às atividades aeróbias de longa duração e intensidade (4,5) . Mas apesar de alguns estudos terem examinado os benefícios e comprometimentos de programas que incluem componentes de força e aeróbio em uma mesma sessão de treinamento, apenas dois experimentos (6,7) verificaram tal efeito em idosos fisicamente ativos, e nenhum até o momento verificou os efeitos agudos promovidos pelo treinamento aeróbio em diferentes intensidades sobre uma sessão de TF em idosos. Dessa forma, algumas lacunas podem ser verificadas a respeito do tema proposto em idosos, dentre elas: a diversificação dos tipos de sujeitos investigados, o tipo de intervenção adotado, e a escassez de experimentos que apresentem protocolos de treino similares aos praticados em academias, e em centros de treinamento.…”
Section: Artigo Originalunclassified
“…Studies investigating CT in the elderly are hardly mentioned in the scientific literature, but some studies have observed that this type of training is capable of developing strength and aerobic capacity 7,8 . Conversely, Cadore et al 9 found that, in elderly males, CT (aerobic before strength training) can negatively interfere with strength gain when the same muscle group is activated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, people who seek to train for muscle hypertrophy have to choose to start the sequence with resistance exercise (Kang and Ratamess 2014). Performing both types of exercise at exactly the same time has not been available although combining aerobics exercise and resistance exercise in one training program has been attempted (Takeshima et al 2004).…”
Section: Introductionmentioning
confidence: 99%